2013
DOI: 10.3389/fneur.2013.00064
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Orthostatic Hypotension in Parkinson’s Disease

Abstract: Orthostatic hypotension (OH) is a common and disabling symptom affecting Parkinson’s disease (PD) patients. We present the effect of the different therapies commonly used to manage PD on this clinical manifestation. For this purpose, we describe the relationship between OH and the current treatments employed in PD, such as L-DOPA, dopaminergic agonists, and continuous dopaminergic stimulation therapies. Additionally, we review the therapeutic measures that could be used to ameliorate OH. There are different ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 147 publications
(249 reference statements)
1
35
0
4
Order By: Relevance
“…[2][3][4] This hypothesis is further confirmed by results of longitudinal studies, which indicate that mortality in PD patients is twice as high as that seen in a population of the same age, mainly due to falls and co-existing cardiovascular diseases. 5,6 Recent reports do not provide consistent evidence to explain an underlying pathology in the cardiovascular system in those with PD. Some researchers support a hypothesis indicating a gradual cardiac sympathetic denervation spreading to other parts of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] This hypothesis is further confirmed by results of longitudinal studies, which indicate that mortality in PD patients is twice as high as that seen in a population of the same age, mainly due to falls and co-existing cardiovascular diseases. 5,6 Recent reports do not provide consistent evidence to explain an underlying pathology in the cardiovascular system in those with PD. Some researchers support a hypothesis indicating a gradual cardiac sympathetic denervation spreading to other parts of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases are the most common cause of death in this group, assumed to be associated with an impaired autonomic control of the cardiovascular system . This hypothesis is further confirmed by results of longitudinal studies, which indicate that mortality in PD patients is twice as high as that seen in a population of the same age, mainly due to falls and co‐existing cardiovascular diseases …”
Section: Introductionmentioning
confidence: 97%
“…Also, it has been shown that a VPAC2 agonist exerts deleterious effects in a stroke model (Darsalia et al, 2013). Those observations are particularly important in the view of neurodegenerative disease treatments because patients with PD present an imbalance of heart autonomic regulation along with orthostatic hypotension (Sanchez-Ferro et al, 2013). Consequently, a PACAP-derived drug useful to treat neurodegenerative diseases must exhibit a potent neuronal anti-apoptotic activity and reduced peripheral effects, especially on the cardiovascular system.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The first step to treat orthostatic hypotension (OH) should be non-pharmacologic methods, such as elastic stockings/abdominal compression bands, fragmentation of meals, increased water and salt intake, avoidance of alcohol consumption, night time head-up-tilt, and physical counter-maneuvers (96). OH is often accompanied by supine hypertension, therefore the treatment should aim at minimizing OH without exacerbating supine hypertension.…”
Section: Autonomic Failurementioning
confidence: 99%